Gene expression in colon cancer: A focus on tumor site and molecular phenotype. Issue 9 (14th July 2015) - Slattery, Martha L.; Pellatt, Daniel F.; Mullany, Lila E.; Wolff, Roger K.; Herrick, Jennifer S.
<x xml:space="preserve">Abstract</x> Hundreds to thousands of genes are differentially expressed in tumors when compared to nontumor colonic tissue samples. We evaluated gene expression patterns to better understand differences in colon cancer by tumor site and tumor molecular phenotype. We analyzed RNA‐seq data from tumor/normal paired samples from 175 colon cancer patients. We implemented a cross validation strategy with nonparametric tests to identify genes which displayed varying expression characteristics related to paired tumor/nontumor tissue across proximal and distal colon sites and by tumor molecular phenotypes, that is, TP53, KRAS, CpG Island Methylator Phenotype (CIMP), and microsatellite instability (MSI). We used Ingenuity Pathway Analysis (IPA) to determine networks associated with deregulated genes in our data. Genes showed significant differences in expression characteristics at the 0.01 level in both validation groups between tumor subsite (116 genes), CIMP high versus CIMP low (79 genes), MSI versus microsatellite stable (MSS) (49 genes), TP53‐mutated versus not mutated (17genes), and KRAS‐mutated versus not mutated (1 gene). Deregulated genes for CIMP high and MSI tumors were often down‐regulated. In contrast to CIMP high and MSI tumors, genes that were deregulated in TP53 were likely to be up‐regulated. ERK1, WNT, growth factors and inflammation‐related factors were focal points of both CIMP and MSI IPA networks. The MUC family of genes was up‐regulated MSI networks. Numerous genes showed differences in expression between proximal and distal tumors, nontumor proximal and distal tissue, and tumor molecular phenotype. Deregulated mucin genes appear to play an important role in MSI tumors. © 2015 Wiley Periodixzcals, Inc.